ANALISIS MOTIVASI PENDORONG WISATAWAN MANCANEGARA BERKUNJUNG KE YOGYAKARTA - Eko Haryanto (Kepariwisataan: Jurnal Ilmiah, 2019)
Tourism is a large travel industry, because it involves a lot of people in the process and contributing a large mount of foreign exchange for the country. People’s decision to travel is influenced by motivation. Knowledge of regarding tourist travel motivation can assist in marketing and product planning and development. Research were related to the push motivation have been carried out in several countries, so it is necessary to do similar research to understand tourist motivation and reason why they come to visit Yogyakarta. This study is to analyse the influence of push motivation of foreign tourists’ decision to visit Yogyakarta. This research found that mostly foreign tourist who visited to Yogyakarta were female than male. They were dominated by 18-30 year old, travel as acouple, with friends and familly member. Push motivation in dimension seeking relaxation is the most significant influent of foreign tourist decision, than follow by gaining knowledge, sightseeing variety, enhancing relation, escaping daily routine and enhancing social circle.in fact fulfilling spiritual needs and fulfilling prestige doesn’t significantly influence of tourist decision to visit Yogyakarta.Keywords: Push Motivation, Foreign Tourist, Tourist Decision, Yogyakarta